Comparison of the efficacy of Schroth and Lyon exercise treatment techniques in adolescent idiopathic scoliosis: A randomized controlled, assessor and statistician blinded study - Bueyuekturan, Oznur; Kaya, Mehmet Hanifi; Alkan, Halil; Buyukturan, Buket; Erbahceci, Fatih (Elsevier, 2024)
Background: Adolescent idiopathic scoliosis (AIS) is the most common vertebral disorder in adolescence. Objectives: The purpose of this study was to compare the effectiveness of Schroth and Lyon exercise methods on Cobb angle (CA), angle of trunk rotation (ATR), quality of life (QoL), and perceived trunk appearance in patients with AIS. Methods: The 31 participants diagnosed (diagnosis age = 12.2 +/- 0.9) with AIS by a physician following the Lenke criteria and subsequently referred to the outpatient clinic were enrolled in the study. All participants were randomly assigned between the Schroth group (SG) and Lyon group (LG) for 6 months of supervised and home treatment. The participants' CA, ATR, Scoliosis Research Society-22 (SRS-22), and Walter-Reed Visual Assessment Scale (WRVAS) were assessed as a baseline, and again following the treatment by the same researcher who remained blinded to the study. Results: In 2-way mixed-design repeated-measures ANOVA analysis, when the change in time was analyzed between the groups (Group x Time [interaction]), a statistical difference was found more significant in SG for the CA-thoracic (F = 103.1, p < .01, 95% CI = 4.1; 2.0 to 6.2), CA-lumbar (F = 19.1, p < .01, 95% CI = 1.7; 1.0 to 2.4), ATR (F = 64.1, p < .01, 95% CI = 1.7; 1.2 to 2.3), and WRVAS (F = 169.5, p < .01, 95% CI = 6.5; 3.2 to 9.9) parameters. The LG was only more significantly improved in the SRS-22 total score (F = 15.7, p < .01, 95% CI =-0.9;-0.2 to-1.6). Conclusion: In the study, The Schroth exercises gave more favorable results than Lyon exercises in terms of CA-T, CA-L, ATR and WRVAS in the conservative treatment of AIS, while Lyon exercises gave more favorable results in terms of QoL. Additionally, according to the results of this study, it was found that the QoL of participants in SG decreased after treatment compared to baseline.
Keywords: Adolescent idiopathic scoliosis; Scoliosis severity; Quality of life; Schroth; Lyon; Conservative treatment